Successful Recovery of Acute Renal Transplant Failure in Recurrent Hepatitis C Virus–Associated Membranoproliferative Glomerulonephritis. Issue 3 (22nd November 2016) - Schrezenmeier, E.; Wu, K.; Halleck, F.; Liefeldt, L.; Brakemeier, S.; Bachmann, F.; Kron, S.; Budde, K.; Duerr, M.
Abstract : Recurrence of hepatitis C virus (HCV)–associated membranoproliferative glomerulonephritis (MPGN) in the kidney transplant may lead to continuous graft deterioration and the need for further renal replacement therapy. The novel direct‐acting antiviral agents (DAAs) allow a highly effective and interferon‐free treatment option for chronic HCV‐infected patients. Data on the therapeutic safety and efficacy in HCV‐infected renal transplant patients are sparse, especially for patients with severe renal impairment. We report the case of a 63‐year‐old female HCV‐positive renal transplant patient with biopsy‐proven recurrence of MPGN in the renal graft 3 years after transplant. Because of rapid loss of transplant function and consecutive need for hemodialysis, we initiated a combined anti‐HCV–directed therapy regimen consisting of daclatasvir and simeprevir over 12 weeks. Viral clearance of HCV was obtained as early as 2 weeks after start of treatment. No adverse therapy‐associated side effects were observed, and immunosuppressive dosing remained unchanged. Importantly, graft function fully recovered and hemodialysis was stopped 2 mo after the end of daclatasvir/simeprevir treatment. We report the first case of successful recovery of dialysis‐dependent renal transplant failure after treatment of recurrent HCV‐associated MPGN in a kidney transplant recipient by curing the underlying HCV infection with a combination of novel DAAs. Abstract : The authors present a report of a 63‐year‐old woman who had acute renal transplant failure requiring hemodialysis because of recurrence of hepatitis C–associated membranoproliferative glomerulonephritis, which was treated with a combination of new direct‐acting antivirals that led to complete recovery of renal function.